2011
DOI: 10.1128/jb.00107-11
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence-Based Analysis Delineates a Clonal Population of Agrobacterium (Rhizobium) radiobacter (Agrobacterium tumefaciens) of Human Origin

Abstract: The genus Agrobacterium includes plant-associated bacteria and opportunistic human pathogens. Taxonomy and nomenclature within the genus remain controversial. In particular, isolates of human origin were all affiliated with the species Agrobacterium (Rhizobium) radiobacter, while phytopathogenic strains were designated under the synonym denomination Agrobacterium tumefaciens. In order to study the relative distribution of Agrobacterium strains according to their origins, we performed a multilocus sequence-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Both the genetic and ST diversity per strain were observed to be exceptionally high in the genus Aeromonas and were much higher than observed for many other environmental bacteria [9,11,34]. Although strains from countries other than France only represented approximately 25% of the total strains of our dataset, the high level of genetic diversity observed validated the non-redundancy and representativeness of our population.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Both the genetic and ST diversity per strain were observed to be exceptionally high in the genus Aeromonas and were much higher than observed for many other environmental bacteria [9,11,34]. Although strains from countries other than France only represented approximately 25% of the total strains of our dataset, the high level of genetic diversity observed validated the non-redundancy and representativeness of our population.…”
Section: Discussionsupporting
confidence: 60%
“…There is evidence that genetic clusters can correspond to ecologically distinct populations and/or host-adapted populations, even when genes that are not related to virulence are considered [9,11-14]. …”
Section: Introductionmentioning
confidence: 99%
“…and agrobacteria were found to occur in these postagricultural soils. The agrobacteria group describes tumour and gall forming Rhizobium species: R./Agrobacterium radiobacter (previous classified as Agrobacterium tumefaciens; Sawada et al 1993;Young et al 2001Young et al , 2003Aujoulat et al 2011). R. radiobacter rarely attacks coniferous seedlings and is only sometimes the cause of dying off in plants (Sinclair et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…It is recently reported that Agrobacterium strains may carry symbiotic (Sym) plasmid and have nodulating activity on legume plants [7,41]. They have been also identified as an opportunistic human pathogens responsible for nosocomial infections [2] and are widely used in biotechnology to produce genetically modified plants [36].…”
mentioning
confidence: 99%
“…The atpD, glnA and rpoB gene fragments were amplified and sequenced as described by Aujoulat et al [2]. The portion of gyrB gene was amplified according to the protocol described by Martens et al [17], and sequenced by using the same primers as for PCR amplifications.…”
mentioning
confidence: 99%